Baseline Household Survey Results: Xai Xai District, Mozambique - Dixon, R. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
International Union for Conservation of Nature (IUCN) carried out household baseline survey in two sites in Mozambique in 2012/2013. This report presents the main results of the analysis of the survey carried out in November 2012 in seven villages, with 140 households, in Xai Xai District, a National Agricultural Research Institute (IIAM) priority site, located in Gaza Province, in the Limpopo river basin, Mozambique. The survey was carried out using the standardised CCAFS household baseline tool. Within the Xai Xai district the site a 10 x 10 km block was selected. A complete and up-to-date list of villages within the block was made. A random sample of seven villages was taken from all those villages in each block. A complete list of households within each selected village was generated. 20 households were selected at random from the list within each village. The CCAFS questionnaire was then used on a total sample of 140 respondents.